PENERAPAN MODEL PEMBELAJARAN PEMECAHAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 005 LENGGADAI HILIR KECAMATAN RIMBA MELINTANG - Efendi Efendi; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The bacground of this research is because of the low mathematical learning result of grade V SDN 005 Lenggadai Hilir, Rimba Melintang subdistrict. Students’ average score is only 60, meanwhile the minimum completeness criteria (KKM) is 65. From 27 students, there are only 12 students that could achieve KKM. This research is the classroom action research (PTK) that has purpose to increase the matematical learning result of grade V SD Negeri 005 Lenggadai Hilir through the application of problem solving learning model. Instruments to collect the data in this research are teacher’s activities, students’ activites and students’ learning results. The results show that there is an increase students’ average score from 60 to 75,5 in the test of cycle I, and increases to 89,60 with 89,9% classical completeness. The average score of students’ activity in the first cycle is 75,2% with good category, increases into 85,2% also with good category in the second cycle. It is similar to students’ activity that is 75% with good category in the first cycle, and increases into 87,5% also with good category in second cycle. Based on this result it can be concluded the the application of problem solving learning model can increase mathematical learning result of grade V SDN 005 Lenggadai Hilir.Keywords: Problem Solving Learning Model, Matematical Learning Result